2010
DOI: 10.1098/rspb.2010.0572
|View full text |Cite
|
Sign up to set email alerts
|

Paternal effects inArabidopsisindicate that offspring can influence their own size

Abstract: The existence of genetic variation in offspring size in plants and animals is puzzling because offspring size is often strongly associated with fitness and expected to be under stabilizing selection. An explanation for variation in seed size is conflict between parents and between parents and offspring. However, for this hypothesis to be true, it must be shown that the offspring genotype can affect its own size. The existence of paternal effects would support this hypothesis, but these have rarely been shown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 75 publications
(96 reference statements)
3
27
0
1
Order By: Relevance
“…This locus shows an average increase of 2.52 seeds when the Col allele is present and explains 6.8% of the variance of the trait (Table II). The identification of a male-mediated seed yield trait in Col/Ler RILs is consistent with experiments that examined paternal effects in seed size and number in reciprocal crosses between different Arabidopsis accessions (see "Discussion"; House et al, 2010).…”
Section: Mapping Of Male and Female Nonrandom Mating Qtls And Analysisupporting
confidence: 58%
See 2 more Smart Citations
“…This locus shows an average increase of 2.52 seeds when the Col allele is present and explains 6.8% of the variance of the trait (Table II). The identification of a male-mediated seed yield trait in Col/Ler RILs is consistent with experiments that examined paternal effects in seed size and number in reciprocal crosses between different Arabidopsis accessions (see "Discussion"; House et al, 2010).…”
Section: Mapping Of Male and Female Nonrandom Mating Qtls And Analysisupporting
confidence: 58%
“…The 2-LOD interval for this QTL maps to the region bounded by markers mi260 and mi123 and encompasses a 18.4-cM region that contains more than 1000 genes. The Col allele at this locus increases the phenotypic value of seed yield per fruit, consistent with data from reciprocal crosses between different accessions of Arabidopsis (House et al, 2010). To study the role of conflict between parents and between parents and offspring, House et al performed a series of reciprocal crosses between four accessions of Arabidopsis, including Col and Ler.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Further research analysing parent-offspring regression and/or family trials should determine the amount of additive variation within the observed genetic variation in SM in this pine species. Because SM has a relevant role in many important life history processes, many studies have focussed on determining the sources of SM variation in different plant species, but the effects of the maternal environment and the maternal genotype have not always been adequately separated (Blodner et al, 2007;Guo et al, 2010), and when they have been separated (Halpern, 2005;Galloway et al, 2009;House et al, 2010), they have usually referred to annual plants (but see Stoehr et al, 1998). Results are very variable.…”
Section: Sm Variationmentioning
confidence: 99%
“…Seeds include tissues of both maternal and embryonic origin, with triploid (or maternal-haploid in gymnosperms) and diploid genetic material. Because of their close connection with the mother plant, seeds are influenced not only by their own genotype (House et al, 2010), but also by the maternal genotype (Schwaegerle and Levin, 1990;Platenkamp and Shaw, 1993;Wolfe, 1995) and by the environmental conditions where the mother plant has grown (Roach and Wulff, 1987). The maternal environmental effect has often been confounded by the effect of the maternal genotype (Vaughton and Ramsey, 1998;Susko and Lovett-Doust, 2000;Voeller et al, 2012;Sober and Ramula, 2013), which, in turn involves both nuclear and extranuclear effects (Lipow and Wyatt, 1999) and can differentially affect the different seed tissues because of their different genetic contributions (Lacey et al, 1997).…”
Section: Introductionmentioning
confidence: 99%